Non-coding RNAs as biomarkers for acute myocardial infarction - WANG Chen; JING Qing (Acta Pharmacologica Sinica, 2018)
Acute myocardial infarction (AMI) is a main threat to human lives worldwide. Early and accurate diagnoses warrant immediate medical care, which would reduce mortality and improve prognoses. Circulating non-coding RNAs have been demonstrated to serve as competent biomarkers for various diseases. Following the identification of cardiac-specific microRNA miR-208a in circulation, more non-coding RNAs (miR-1, miR-499 and miR-133) have been identified as biomarkers not only for the diagnosis of AMI but also for prognosis post infarction. Here, we summarized recent findings on non-coding RNAs as biomarkers for early diagnosis of ST-segment elevation myocardial infarction and for disease monitoring of myocardial infarction. In addition, the prognostic potential of non-coding RNAs in patients treated with percutaneous coronary intervention was also described. We also include studies based on biobanks, and build a miRNA release spectrum after AMI, which provides quantitative and time-lapse monitoring of AMI progress. With this spectrum, we are able to customize personal medical care, which prevents further damage. By constructing a network of circulating non-coding RNAs with high specificity and sensitivity, detailed diagnostic information was provided for personalized medicine. Unveiling the roles and kinetics of circulating non-coding RNAs may lead to a revolution in clinical diagnosis.